Rancang Bangun Game Edukasi ”Assemble & Learn” Berbasis Android sebagai Media Interaktif pada Materi Perakitan Komputer untuk Siswa SMK - M. Ismail; Dedy Irfan; Agariadne Dwinggo Samala; Mahesi Agni Zaus (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The limited use of interactive learning media has made it difficult for students to visualize the functions and assembly flow of computer components. This study aims to design and develop an Android-based educational game called “Assemble & Learn” as an interactive medium for computer assembly lessons, specifically for vocational high school students at SMK Negeri 1 Tanjung Jabung Barat. The development process follows the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, testing, and distribution. The learning content covers several core competencies: KD 3.2/4.2 on computer assembly, KD 3.3/4.3 on assembly testing, KD 3.4/4.4 on BIOS configuration, and KD 3.5/4.5 on operating system installation, with a focus on KD 3.2 and KD 3.5. Research instruments consist of validation questionnaires for subject-matter experts, media experts, and student trials using the System Usability Scale (SUS). Validation results show that the educational game received an average score of 94% from media experts and 100% from subject-matter experts, both categorized as “Highly Feasible.” Meanwhile, student trials indicated strong acceptance, with an average SUS score of 85% (excellent usability). In conclusion, the “Assemble & Learn” educational game offers an innovative solution to boost learning motivation, simplify material visualization, and provide flexible practice opportunities, thereby supporting the achievement of computer assembly competencies in an optimal and effective way.